Right of the line: The president's bodyguard - Edited by Chhina, Rana T.S.; chandra, Yashaswini (Ed.) (New Delhi Publications Division, Ministry of Information and Broadcasting, GOI, 2015)
Right of the Line.
Keywords: President House; President's Bodyguard